LESSONS OF PHYSICAL EDUCATION IN COAST SCHOOL: DESCRIPTION OF A REALITY FROM THE LOOK OF THE PUPILS (Fiep Bulletin - online, 2013)
This work is a descriptive study, that had as objective to discourse on the lessons of Physical Education, developed in a marginal school of the City of Porto Velho - Rondônia. The sample composes in 52 students, regularly registered of 1° to 5° year of basic education. The information had been collected from the job of a questionnaire with opened questions, evolved questions relate all to the preference of the pupils for the activities developed during the school year. The results suggest that: ) the activities that the pupils more would like to practice are: swimming, futsal, soccer, activities with ropes, volleyball, dance, ground gymnastics and to play of doll; b) The ones that had more liked to practice had been: motor games, ground soccer, gymnastics, activities with rope, race/jump (atletismo), forest fire, volleyball, lengthening, abdominal and handball e; c) The ones that had not liked to participate had been: ground race, gymnastics, lengthening, soccer, activities with arc, wheel songs. The study it considered important to verify the opinion of the pupils so that the planning goes of meeting with its expectations and necessities, therefore offering more pleasant activities becomes next the acceptance possibility of the limitations imposed for the game situations, of tolerance to the small frustrations, the individual limitations, contribution and participation in the activities with enthusiasm.
Keywords: pertaining to school physical education; content; students